The size and strength development in elite youth ice hockey players - Leiter, J. R.; Cordingley, D. M.; Zeglen, A. J.; Carnegie, G. D.; MacDonald, P. B. (International Journal of Kinesiology & Sports Science, 2016)
Ice hockey is a fast, physical sport that requires high levels of muscular strength, muscular endurance and agility. Objectives: This study was conducted to create a profile including: anthropometric measurement, muscular strength, muscular endurance, lower body jump height and distance, and agility characteristics for elite youth hockey players. Methods: Pre-season off-ice testing results were retrospectively reviewed from a human performance database. Variables included height, weight, body fat percentage, grip strength, push-ups/bench press, supine rows, the plank test, vertical jump, standing long jump, hip adductor and abductor strength, and the 5-10-5 shuttle, and. One-way ANOVAs (1group x 4 time) and Tukeys post-hoc tests were performed to determine changes in the immediately successive age group (p<0.05). Results: Participants included male Bantam-(age: 13-14) and Midget-(age: 15-17) AAA ice-hockey players (n=260). Age categories were grouped as 13 years old (yo)(n=75), 14 yo (n=70), 15 yo (n=58), and 16-17 yo (n=57). Increases between successive age groups were observed in the following variables: weight (13, 14, 15 and 16-17 yo), height (13 and 14 yo), left and right grip strength (13, 14, 15, and 16-17 yo), bench press (15 and 16-17 yo), left and right hip abduction (14, 15, and 16-17 yo), and vertical and standing long jump (13, 14, and 15 yo). Total time for the 5-10-5 shuttle run test decreased from 13 to 14yo, and 14 to 15 yo. Conclusion: Changes with age in office performance variables of elite amateur hockey players should be recognized, followed, and addressed during player development to maximize the potential for elite performance and reduce the risk of injury.